Wait for dark - Hooper, Kay (A Bishop/SCU novel, 2017)
"An SCU team investigates a string of accidents, only to uncover a deadly and deliberate monster in the latest novel from New York Times bestselling author Kay Hooper. In Clarity, North Carolina, the residents have fallen victim to an unfortunate series of events. Seemingly random accidents have taken the lives of several citizens in the small mountain town. But these deadly coincidences are anything but. Something is on the hunt in Clarity, and the only clue as to what is a cryptic note given to the victims 24 hours before they meet their ends: "Wait for dark." Sheriff Mal Gordon knows how to handle his town, but he has no idea how to handle this. Hollis Templeton and her team from the Special Crimes Unit, including her partner and lover, telepath Reese DeMarco, are called in to investigate. But while the SCU has prepared them for the unknown, the incredible evil stalking Clarity shakes the team to its core when one of their own is targeted. Now Hollis, the "cat with nine lives" finds herself facing death again. And this time, not even her partner can protect her."--